Utilization of Probiotic-Fermented Rice Straw as Ruminant Feed - Thalib, Amlius (Indonesian Bulletin of Animal and Veterinary Sciences, 2008)
Agriculture in Indonesia is dominated by a rice-based farming system where ruminants are kept as saving and to provide draft power. The productivity of ruminants under this farming system is relatively low. The low productivity is mainly due to inadequate supply of feed. As the agriculture is a rice-based farming system, rice straws become potential crop residues existing in almost all areas in Indonesia. Many studies on the utilization of rice straw as ruminant feed have been conducted. Rice straw has very low nutritive values, especially its crude protein content and digestibility. A lot of treatments have been applied to improve the  nutritional  values  particularly  the  digestibility  value,  that is,  by  means  of  physical,  chemical  and  biological treaments. In recent studies, the efficiency of rice straw utilization for ruminants was improved by supplementation of probiotic. The aim of probiotic addition is to enhance the ability of rumen microbes to digest the rice straw in the rumen by their synergistic effect. The methods of probiotic addition can be introduced into rice straw through fermentation process or mixed with the concentrates. This paper exposes the utilization of probiotic-fermented rice straw for ruminant animals and their storage system.   Key words: Rice straw, fermentation, probiotic, ruminants